1990
DOI: 10.1016/0016-6480(90)90026-i
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in plasma levels of gonadal steroids of sea bass, Dicentrarchus labrax L

Abstract: Levels of plasma testosterone (T) and 11-ketotestosterone (11-KT) in males and plasma 17 beta-estradiol (E2), 17 alpha-20 beta-dihydroxy-4-pregnen-3-one (17 alpha,20 beta-diOH-P), and T in females were assayed by radioimmunoassay at monthly intervals throughout the sexual cycle of sea bass (Dicentrarchus labrax L.). 17 alpha,20 beta-DiOH-P was maintained at low levels (below 1 ng/ml) throughout the year, even during the spawning period (January-March). A bimodal seasonal pattern of plasma testosterone was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
77
0
16

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(114 citation statements)
references
References 33 publications
21
77
0
16
Order By: Relevance
“…First, in some species with which we are . Numbers refer to the following species: 1, Acipenser ruthenus (Mojazi Amiri et al, 1996); 2, Oncorhynchus mykiss (Rouger and Liley, 1993); 3, Oncorhynchus nerka (Kubokawa et al, 1999); 4, Salmo salar (Mayer et al, 1990b); 5, Salmo trutta (Cardwell et al, 1996); 6, Salvelinus fontinalis (Cardwell et al, 1996); 7, Cyprinus carpio (Nikitina and Godovich, 1984); 8, Catostomus commersoni (Scott et al, 1984); 9, Ictalurus nebulosus (Rosenblum et al, 1987); 10, Heteropneustes fossilis (Lamba et al, 1983); 11, Fundulus heteroclitus (Cochran, 1987); 12, Porychthys notatus (Knapp et al, 1999); 13, Gasterosteus aculeatus (Mayer et al, 1990a); 14, Syngnathus acus (Mayer et al, 1993); 15, Syngnathus typhle (Mayer et al, 1993); 16, Lates calcarifer (Guiguen et al, 1993); 17, Dicentrarchus labrax (Prat et al, 1990); 18, Morone saxatilis (Mylonas et al, 1997); 19, Lepomis macrochirus (Kindler et al 1989); 20, Stizostedion vitreum (Malison et al, 1994); 21, Pomatomus saltator (MacGregor et al, 1981); 22, Pagrus major (Ouchi et al, 1988); 23, Acanthopagrus butcheri (Haddy and Pankhurst, 1998); 24, Rhabdosargus sarba (Yeung and Chan, 1987); 25, Sparidentex hasta (Lone et al, 1991); 26, Cynoscion nebulosus (Thomas et al, 1982); 27, Oreochromis aureus (Mol et al, 1994); 28, Oreochromis mossambicus ; 29, Sarotherodon melanotheron ; 30, Chromis dispilus (Pankhurst, 1990); 31, Acanthochromis polyacanthus (Haddy and Pankhurst, 1998); 32, Hypsypops rubicundus (Sikkel, 1993); 33, Sparisoma viridae (Cardwell and Liley, 1991); 34, Parablennius sanguinolentus parvicornis …”
Section: Mating Systems and Endocrine Responsivenessmentioning
confidence: 99%
“…First, in some species with which we are . Numbers refer to the following species: 1, Acipenser ruthenus (Mojazi Amiri et al, 1996); 2, Oncorhynchus mykiss (Rouger and Liley, 1993); 3, Oncorhynchus nerka (Kubokawa et al, 1999); 4, Salmo salar (Mayer et al, 1990b); 5, Salmo trutta (Cardwell et al, 1996); 6, Salvelinus fontinalis (Cardwell et al, 1996); 7, Cyprinus carpio (Nikitina and Godovich, 1984); 8, Catostomus commersoni (Scott et al, 1984); 9, Ictalurus nebulosus (Rosenblum et al, 1987); 10, Heteropneustes fossilis (Lamba et al, 1983); 11, Fundulus heteroclitus (Cochran, 1987); 12, Porychthys notatus (Knapp et al, 1999); 13, Gasterosteus aculeatus (Mayer et al, 1990a); 14, Syngnathus acus (Mayer et al, 1993); 15, Syngnathus typhle (Mayer et al, 1993); 16, Lates calcarifer (Guiguen et al, 1993); 17, Dicentrarchus labrax (Prat et al, 1990); 18, Morone saxatilis (Mylonas et al, 1997); 19, Lepomis macrochirus (Kindler et al 1989); 20, Stizostedion vitreum (Malison et al, 1994); 21, Pomatomus saltator (MacGregor et al, 1981); 22, Pagrus major (Ouchi et al, 1988); 23, Acanthopagrus butcheri (Haddy and Pankhurst, 1998); 24, Rhabdosargus sarba (Yeung and Chan, 1987); 25, Sparidentex hasta (Lone et al, 1991); 26, Cynoscion nebulosus (Thomas et al, 1982); 27, Oreochromis aureus (Mol et al, 1994); 28, Oreochromis mossambicus ; 29, Sarotherodon melanotheron ; 30, Chromis dispilus (Pankhurst, 1990); 31, Acanthochromis polyacanthus (Haddy and Pankhurst, 1998); 32, Hypsypops rubicundus (Sikkel, 1993); 33, Sparisoma viridae (Cardwell and Liley, 1991); 34, Parablennius sanguinolentus parvicornis …”
Section: Mating Systems and Endocrine Responsivenessmentioning
confidence: 99%
“…Also, several reports have demonstrated that the entire process of vitellogenesis is regulated by E2 (Nagahama, 1994) and it has been described the stimulatory effect of FSH on the activity and expression of P-450 aromatase in vitellogenic trout follicles, suggesting that FSH plays a fundamental role in the regulation of E2 production in salmonid ovary . In the sea bass, plasma levels of 11-KT and T increase during the spermatogenesis period (October-January) (Prat et al, 1990; and plasma levels of E2 increase in parallel with the vitellogenin and the oocyte growth . The results obtained in this study are consistent with the expression profile seen for sbsFSHR in testis and ovary of adult sea bass, since high levels of sbsFSHR mRNA were observed in October in males and a significant increase in the expression of this gene was appreciated in October-November in females.…”
Section: Discussionmentioning
confidence: 99%
“…El E2 producido estimula la síntesis hepática de VTG que es transportada al ovario para ser incorporada a los oocitos en crecimiento (Nagahama, 1994). En la lubina, los niveles plasmáticos de T y E2 aumentan en paralelo conforme avanza el crecimiento oocitario y disminuyen durante la época de puesta, describiendo un perfil plasmático similar al de VTG Asturiano et al, 2002;Prat et al, 1990). Una vez completada la vitelogénesis, antes de la maduración del oocito, la LH induce un giro en la actividad esteroidogénica del ovario.…”
Section: Esteroidogénesisunclassified
See 2 more Smart Citations